Adult CNP::EGFP transgenic mouse shows pronounced hypomyelination and an increased vulnerability to cuprizone-induced demyelination - Millet, Violeta (2012)
CNP::EGFP transgenic mice, genetically engineered to express the enhanced green fluorescent protein (EGFP) under the control of the 2-3-cyclic nucleotide 3-phosphodiesterase (CNPase) promoter in oligodendroglial and Schwann cells, constitute a very important and widely used tool for the study of oligodendrocyte (OLG) development and function in young mice. We have compared the vulnerability of adult CNP::EGFP and wild type (WT) mice to cuprizone (CPZ)-induced demyelination. CNP::EGFP mice were significantly more susceptible to CPZ-induced demyelination evaluated by MBP immunostaining, oligodendroglial progenitor cell (OPC) recruitment and astroglial, microglial and nestin response. This enhanced vulnerability was due to the presence of a basal demyelination in these adult transgenic mice. CNP::EGFP control mice displayed a significant decrease in corpus callosum (CC) thickness and MBP immunoreactivity. Morphometric analysis showed a significant decrease in the frequency of myelinated axons, myelin turns (lamellae) and g-ratio carried out in the optic nerve (ON) and CC of CNP::EGFP as compared to WT mice. Moreover, our results showed a decrease in the number of axons of small caliber, concomitantly with an increase in the number of axons of bigger size with more and enlarged mitochondria, which suggests a high energy demand. These findings and those displaying that MBP+ cells and NF200 staining in the CNP::EGFP cortex were more sparsely distributed provide  evidence of axonal loss. Supporting these findings, a decreased number of NeuN+ cells was observed in the CA3 fields of the hippocampus. An increase in microglial and astroglial basal activation was observed in these animals, accompanied by enhanced lipid peroxidation and morphologically altered OPC recruitment. A more important reduction in the CNPase protein relative to MBP was determined in the CC, which indicates an altered pattern in the relative composition of myelin proteins and a deficient expression of CNPase. Behavioural analysis of adult CNP::EGFP transgenic mice supported our results, since it revealed a decrease in locomotion, exploratory activity and motor impairment, as compared to their WT littermates. Our data highlight the relevance of confronting results obtained in adult CNP::EGFP mice against other ones evaluated in WT mice. Adult CNP::EGFP mice could be a useful tool to evaluate future therapies for demyelinating diseases such as Multiple Sclerosis (MS), since these animals present chronic demyelination with axonal degeneration, a characteristic of such pathologies.